PENGARUH KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN TAKSI BLUE BIRD - Lily Harjati, MM; Muhammad fuad (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2016)
With increased rapid transportation industry now makes competition between companies is getting tight in snatch customers as well as maintain existing market share. The good companyâ€™s service and pricing is a unity that can be seen from the customer's expectations. Therefore service companies should continue to seek customer satisfaction in particular with the quality of service and the best price which is the overall impression upon performance of the company. In this research also use three main variable that is service quality, price perception and customer satisfaction variable.The objective of this research are to (1) quality of service Blue Bird taxi, (2) Customer Price Perception in Blue Bird Taxi, (3) The Blue Bird Taxiâ€™s customer satisfaction, (4) the influence of the quality of service and Price Perceptions towards customer satisfaction of Blue Bird Taxi. The method used is the judgment sampling with a respondent of 100 people who have used the Blue Bird Taxi. Â The results showed that: (1) the level of quality of services provided to the customers of the Blue Bird taxi is good. (2) the customer agrees that the perception the price against the Blue Bird taxi is in accordance with the details of the questions on the questionnaire. (3) Customer Blue Bird taxi satisfied service quality and prices will be given to the customer, (4) the quality of service of positive and significant effect against customer satisfaction in Blue Bird taxi. (5) Price perceptions of positive and significant effect against customer satisfaction in Blue Bird taxi.The management of Blue Bird needs to make continuous improvements and innovate in order to increase customer satisfaction and loyalty.